Síndrome de Waardenburg. Presentación de un caso. - Valledor, Teodosio; Borbolla, Liane; Hernández, Pedro; Urquiza, Lilia; Valdés, Orestes (Revista Cubana de Pediatría, 2022)
Reporte de un caso en Cuba.